Determination of factors related to the abandonment of the practice of swimming by former costa rican swimmers - Víquez Ulate, Fabián (2007)
The objective of this study was to determine the importance of different dimensions as the possible causes for the abandonment of the practice of swimming by former Costa Rican swimmers.  Subjects: 51 former swimmers participated, including 17 men (22 ±3.4 years of age) and 34 women (22.5 ±3.4 years of age) from different Costa Rican swimming teams.  The Questionnaire of Reasons for Attrition in the Practice of Sports (Gould et al, 1982; cited by Salguero, Tuero, and Márquez, 2003) was used.  Results:  A positive relationship was noted between perceptions of low skill and low performance (r: 0.372), while negative relationships were noted between years of practice and low skill (r:-0.337), years of practice and influence from others (r:-0.286), and years of practice and starting age for swimming (r:-0.622).  A significant interaction was found in the dimensions gender of participants (F: 2.952; p<0.05) and starting age for swimming (F: 3.147; p<0.01).  An interaction was also found between dimensions and the desire to swim again (F: 2.485; p>0.05).  There were also significant differences in the years of practice; that is, subjects who started before the age of 10 had a higher average of years of practice than those who started later (F: 21.465; p<0.05).  Additionally, a significant interaction was found in weekly hours of swimming practice (F: 2.072; p<0.05).  There were no significant differences (F: 2.535; p>0.05) according to weekly hours of training when subjects were actively swimming. Conclusions: Possible reasons for dropping out were lack of enjoyment and poor physical condition for men and perception of lack of team spirit for women.  The group that started after the age of ten gives similar importance to all the dimensions as possible reasons for dropping out, while the group that began swimming before the age of ten sees lack of team spirit, lack of enjoyment, and poor physical condition as the key reasons for dropping out.  The most important dimensions that represented the reasons for abandonment in subjects who wanted to swim again were lack of team spirit, poor physical condition and low skill, while lack of enjoyment was the most important reason for subjects who do not want to swim again.  In the group of subjects who would swim less than six hours, lack of team spirit is the most important cause, while the dimension lack of enjoyment was the most important reason for subjects who would swim 6 to 12 hours.  Additionally, the highest dropout percentages were observed in the transition from secondary school to college.